2021
DOI: 10.3390/cancers14010027
|View full text |Cite
|
Sign up to set email alerts
|

HIF-Dependent CKB Expression Promotes Breast Cancer Metastasis, Whereas Cyclocreatine Therapy Impairs Cellular Invasion and Improves Chemotherapy Efficacy

Abstract: The oxygen-responsive hypoxia inducible factor (HIF)-1 promotes several steps of the metastatic cascade. A hypoxic gene signature is enriched in triple-negative breast cancers (TNBCs) and is correlated with poor patient survival. Inhibiting the HIF transcription factors with small molecules is challenging; therefore, we sought to identify genes downstream of HIF-1 that could be targeted to block invasion and metastasis. Creatine kinase brain isoform (CKB) was identified as a highly differentially expressed gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The CKB gene is located on chromosome 14q32.33 and consists of seven exons [30] . CKB has been reported to exhibit abnormal expression in malignant tumors like prostatic cancer and breast cancer and play a pivotal role in tumorigenesis [ 31 , 32 ]. However, it's function has not been reported in ccRCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CKB gene is located on chromosome 14q32.33 and consists of seven exons [30] . CKB has been reported to exhibit abnormal expression in malignant tumors like prostatic cancer and breast cancer and play a pivotal role in tumorigenesis [ 31 , 32 ]. However, it's function has not been reported in ccRCC.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, a series of experiments confirmed that IGF2BP2 bound to CKB mRNA to enhance its stability, and then promoted the expression of CKB. Several studies have reported significant differences in CKB expression in malignancies such as prostate cancer and breast cancer, emphasizing its crucial role in tumor progression [ 31 , 32 ]. Nevertheless, the biological function and mechanism in ccRCC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the negative correlation with creatine phosphate could also implicate that OC cells obtained their ATP mostly via fatty acid oxidation once they metastasized in the omentum. Overexpression of creatine kinase B (CKB) takes place in breast, colorectal, and OCs in response to acute hypoxia exposure [ 73 75 ] due to more ATP production demand for proliferation [ 52 , 76 , 77 ], which means hypoxic OC cells can elevate glucose consumption and lactate production, and decreased ROS production by CKB [ 78 ]. However, lactate production decreased or had a low negative correlation with pH, indicating less active glycolysis.…”
Section: Discussionmentioning
confidence: 99%